81st EAGE Conference and Exhibition 2019 2019
DOI: 10.3997/2214-4609.201901513
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Classification of Geologic Units in Seismic Images Using Partially Interpreted Examples

Abstract: Geologic interpretation of large seismic stacked or migrated seismic images can be a time-consuming task for seismic interpreters. Neural network based semantic segmentation provides fast and automatic interpretations, provided a sufficient number of example interpretations are available. Networks that map from image-to-image emerged recently as powerful tools for automatic segmentation, but standard implementations require fully interpreted examples. Generating training labels for large images manually is tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The number of channels varies from six up to 32. In a similar experiment, Peters et al [2019a] showed that it is possible to obtain high-quality segmentations of the seismic images provided there are a sufficient number of known labeled columns. Here we will use lithology information from just two wells per image.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of channels varies from six up to 32. In a similar experiment, Peters et al [2019a] showed that it is possible to obtain high-quality segmentations of the seismic images provided there are a sufficient number of known labeled columns. Here we will use lithology information from just two wells per image.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Peters et al [2018Peters et al [ , 2019a introduced partial loss-functions for non-linear regression and classification for seismic interpretation. These type of loss functions measure misfit at the known and sparsely distributed annotated label pixels only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…are the labeled features that need to be recovered. Using deep convolution networks is therefore a straight forward extension of existing neural network technology and have been studied recently by many authors (see for example [Peters et al, 2018, 2019, Wu and Zhang, 2018, Waldeland et al, 2018, Poulton, 2002, Leggett et al, 2003, Lowell and Paton, 2018, Zhao, 2018 and references within). However, while it seems straight forward to use such algorithms, there are some fundamental differences between vision-related applications to seismic processing.…”
Section: Introductionmentioning
confidence: 99%